THE ENLIGHTENMENT PERIOD IN ENGLISH LITERATURE - Nematilloeva Farangiz Mohammadi (Western European Studies, 2024)
The Enlightenment period in English literature, is a fascinating time. The Enlightenment, also known as the Age of Reason, was an intellectual and cultural movement that flourished in Europe from the late 17th to the 18th century. It was characterized by a focus on reason, scientific inquiry, individualism, and skepticism of traditional authority. Enlightenment thinkers emphasized the power of reason and logic in understanding the world. This rational approach influenced literature by promoting clear, logical writing and arguments
Keywords: enlightenment; age of reason; individualism; skepticism